Gated community, theory and implementation in landscape and housing area of Malaysia - Abdul Malek, Nurhayati; Ibrahim, Mansor (2010)
The interpretation of gated community in Malaysia often been regarded as a residential community area equipped with human or electronic security surveillance. However, the true meaning is a community area enclosed by walls and fences, most of the time having controlled over the entrances especially for automobiles and pedestrians. It is an issue where the concept was only used for profit gaining and not looking at the holistic approach towards overall community planning and the landscape environment.